A Analisis Item Instrumen Kesadaran Diri, Motivasi, dan Perencanaan Karir Pendidik Menggunakan Aplikasi SPSS - Handoko, Handoko (Universitas Muhammadiyah Surabaya, 2024)
The study aims to analyze instruments related to self-confidence, motivation, and career planning in education. A well-designed instrument must be free from bias to prevent misinterpretation during use. Errors in instrument design can lead to invalid results. Therefore, instrument validation is necessary to ensure optimal outcomes. The research was conducted on students majoring in educational sciences within the faculty of teacher training and education. A total of 100 respondents from various study programs participated in the pilot test. The instrument consists of 90 items divided across three variables with seven indicators. The validity and reliability of the instruments will be evaluated, and those that do not meet the criteria will be excluded to maintain the quality of the research.